A FRAMEWORK OF STRATEGIC COMMUNICATION FOR GOVERNMENT OF PAKISTAN: NATIONAL AND INTERNATIONAL CONCEPTS AND MANIFESTATIONS - Dilavez Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
Strategic communication (StratCom forthwith) is growing in importance because countries need a planned communication campaign. For a country like Pakistan, it is even more important to have a StratCom policy. On one hand, the strategic geopolitical location of Pakistan poses several security threats to the country like proxy wars, terrorism, sectarian manifestations from within and outside, and organized social crimes, destabilizing the national progress. On the other hand, Strategic communicators are rarely found equally prepared to respond to seen and unforeseen situations. This paper, therefore, analyzes the concept and manifestation of StratCom in Pakistan while presenting challenges to, considerations for, and key principles for developing a framework for StratCom in Pakistan. The paper, therefore, is an attempt to suggest a framework for effective StratCom in Pakistan that could help the country achieve its strategic objectives and sustainable development goals.